Biological dose and complication probabilities for the rectum and bladder based on linear energy transfer distributions in spot scanning proton therapy of prostate cancer. (2nd November 2017) - Pedersen, Jesper; Petersen, Jørgen B. B.; Stokkevåg, Camilla H.; Ytre-Hauge, Kristian S.; Flampouri, Stella; Li, Zuofeng; Mendenhall, Nancy; Muren, Ludvig P.
Abstract: Background: The increased linear energy transfer (LET) at the end of the Bragg peak causes concern for an elevated and spatially varying relative biological effectiveness (RBE) of proton therapy (PT), often in or close to dose-limiting normal tissues. In this study, we investigated dose-averaged LET (LETd ) distributions for spot scanning PT of prostate cancer patients using different beam angle configurations. In addition, we derived RBE-weighted (RBEw ) dose distributions and related normal tissue complication probabilities (NTCPs) for the rectum and bladder. Material and methods: A total of 21 spot scanning proton plans were created for each of six patients using a prescription dose of 78 Gy(RBE1.1 ), with each plan using two 'mirrored' beams with gantry angles from 110°/250° to 70°/290°, in steps of 2°. Physical dose and LETd distributions were calculated as well as RBEw dose distributions using either RBE = 1.1 or three different variable RBE models. The resulting biological dose distributions were used as input to NTCP models for the rectum and bladder. Results: For anterior oblique (AO) configurations, the rectum LETd volume and RBEw dose increased with increasing angles off the lateral opposing axis, with the RBEw rectum dose being higher than for all posterior oblique (PO) configurations. For PO configurations, the corresponding trend was seen for the bladder. Using variable RBE models, the rectum NTCPs were highest for the AO configurations with up to 3% for the 80°/280° configuration while the bladder NTCPs were highest for the PO configurations with up to 32% for the 100°/260°. The rectum D1cm 3 constraint was fulfilled for most patients/configurations when using uniform RBE but not for any patient/configuration with variable RBE models. Conclusions: Compared to using constant RBE, the variable RBE models predicted increased biological doses to the rectum, bladder and prostate, which in turn lead to substantially higher estimated rectum and bladder NTCPs.